2019
DOI: 10.1111/jep.13181
|View full text |Cite
|
Sign up to set email alerts
|

Unwarranted clinical variation in health care: Definitions and proposal of an analytic framework

Abstract: Rationale, aims, and objectives: Unwarranted clinical variation is a topic of heightened interest in health care systems around the world. While there are many publications and reports on clinical variation, few studies are conceptually grounded in a theoretical model. This study describes the empirical foundations of the field and proposes an analytic framework. Method: Structured construct mapping of published empirical studies which explicitly address unwarranted clinical variation.Results: A total of 190 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
121
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(122 citation statements)
references
References 40 publications
1
121
0
Order By: Relevance
“…Findings from this study support the results of earlier research, suggesting incongruences in hand hygiene practices before and after patient care (Ding et al, ). Yet, in comparing practice variations across contexts, it is important to separate contextual factors that are outside the direct control at that level and those that are amenable to change (Sutherland & Levesque, ). Clearly, inconsistencies in practices may be due to environmental factors outside of the control of healthcare providers, viz, time constraints, skill mix, workload and patient acuity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings from this study support the results of earlier research, suggesting incongruences in hand hygiene practices before and after patient care (Ding et al, ). Yet, in comparing practice variations across contexts, it is important to separate contextual factors that are outside the direct control at that level and those that are amenable to change (Sutherland & Levesque, ). Clearly, inconsistencies in practices may be due to environmental factors outside of the control of healthcare providers, viz, time constraints, skill mix, workload and patient acuity.…”
Section: Discussionmentioning
confidence: 99%
“…It is often accepted that wound care practices are influenced by various local factors, and not just the evidence. For instance, the resources available, skill mix, clinician preferences, patient behaviour and length of hospital stay contribute to practice variation (Sutherland & Levesque, ). A systematic review of medical practice variation in developed countries identified 836 published studies and detailed variation across regions, hospitals and physician practices in almost every surgical field, condition and procedure (Corallo et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Countries including the United States of America (USA), Canada, Spain, United Kingdom (UK), Germany, the Netherlands, Norway, New Zealand and Australia have produced atlases of variation in health care to guide system and service improvements [4][5][6]. Through these atlases, substantial variations in the healthcare provided to patients have been identified across each country, with implications for patient outcomes [7]. Variations have been reported in a range of care areas including surgery for hysterectomy, cataract surgery, planned Caesarian section, arthroscopic surgery and potentially preventable hospitalisations for selected conditions [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Unwarranted clinical variation (UCV) describes "patient care that differs in ways that are not a direct and proportionate response to available evidence; or to the healthcare needs and informed choices of patients." [7] Understanding variation and what is unwarranted has been identified as important in guiding valuebased healthcare [8,11]. Value-based healthcare has been conceptualised in the US context in terms of the 'health outcome achieved per dollar spent,' but more recently in the UK in terms of optimising the value of resources through their utilisation for each patient sub-group, which is determined by clinicians [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Medical practice variation is unwarranted if it cannot be explained by patient characteristics or patient preference [9,10]. To identify unwarranted practice variation, studies should compare study groups that are comparable in terms of relevant patient characteristics or make them comparable through careful case-mix correction [11]. Patient preference is important when both modes of deliveryvaginal delivery and caesarean sectionare an acceptable option.…”
Section: Introductionmentioning
confidence: 99%